华人移民论述研究 ：以 (1930-2009) 年新马华校历史教科书为研究对象 = Chinese migration narratives in Singapore and Malaysia Chinese history textbooks (1930-2009） - 李宜恩 Lee, Yi Ern (2016)
20世纪初，新加坡和马来亚新式华文教育的崛起，使两地华校对教科书的需求增加。对华裔子弟而言，华校历史课本是了解祖先南来历史的重要方式。而历史教科书作为型塑思想、观念的关键手段，自然受到当权者的管制。因此，教科书内关于中国人移居南洋的历史叙述，必然符合当代的意识形态。另外，新马时局的变革很大程度影响教科书所采用的叙述视角。本研究搜集从民国时期至现代的华校历史教科书，并针对教材内中国人南移的历史叙述进行分析。首先，本文将所得的历史教材分成三个研究时期，即民国至二战前（1930-1942）、二战后至自治独立前（1945-1956）和自治独立后至现代（1957— 2009）。本研究通过分析历史教材的出版概况和论述内容，探讨80年历史教科书的嬗变如何呈现时代的变革。不仅如此，教材随着历史脉络的变迁，也反映华人身份认同的转变。本研究希望能通过36本教材的分析，研究华校历史教科书在新马两地的政治功能。而学界鲜少以历史教科书的视角，探索新马华人移民的课题。本文希望能以此为华人移民议题开辟另一研究途径。New Education from China was imported to Malaysia and Singapore in the early 20th century and the demand of Chinese textbooks increased rapidly. History textbooks from Chinese schools are an important source for Malaysia and Singapore Chinese to know how their ancestors immigrated to Nanyang. History textbooks are known as a tool for propaganda. Hence, this segment history where Chinese immigrate to Nanyang has to suit the ideology that supported by authority in each historical period. Social changes of Malaysia and Singapore have affected the narrative perspectives of history textbooks. This study used Malaysia and Singapore Chinese School’s textbooks, ranging from 1930 to 2009, to analyze the history of Chinese immigration. Firstly, the texts were divided into three periods, which are 1930 to 1942, 1945 to 1956 and 1957 to 2009. This study aims to understand how the change of textbook in 80 years reflects social changes by analyzing publishing markets and historical discourses. While the change of textbook may be seen as a change in text, but it actually goes deeper in reflecting the transformation of Malaysia and Singapore Chinese identities. This study points to the political function in history textbook by analyzing 36 textbooks. In addition, little research has been done about the Chinese migrants from the perspective of Chinese history textbook. This study proposes a new method in understanding Chinese migrant movement.